Autoamputation of Fingers — A Rare Presentation of Tethered Cord after Early Repair of Cervicothoracic Myelomeningocele - Venkata Ramesh Chandra Vemula; Chandramowliswara Prasad Bodapati; Jayachandar Vuttarkar; Sanjeev Akula; Krishnamohan Chennati (Indian Journal of Neurosurgery)
Abstract Dorsal myelomeningoceles are rare but well-recognized lesions. The phenomenon of the cord tethering at the operative site several years after surgery is known. Self-mutilation of the fingers as the presenting symptom of such tethered cord is extremely rare with only one case reported in literature. We report a 14-year-old girl with past history of undergoing dorsal myelomeningocele repair at birth presenting with history of nonhealing ulcer at the proximal phalanx of the little finger and the absence of the middle and distal phalanges. Imaging revealed tethering of the cord at the previous surgical site. She underwent exploration of the surgical site and detethering of the cord yielding good results. The clinical, radiological, and operative findings are discussed.